Rehabilitation of spatial neglect by prism adaptation: a peculiar expansion of sensorimotor after-effects to spatial cognition. - Jacquin-Courtois, S; O'Shea, J; Luauté, J; Pisella, L; Revol, P; Mizuno, K; Rode, G; Rossetti, Y (2013)
Unilateral neglect is a neurological condition responsible for many debilitating effects on everyday life, poor functional recovery, and decreased ability to benefit from treatment. Prism adaptation (PA) to a right lateral displacement of the visual field is classically known to directionally bias visuo-motor and sensory-motor correspondences. One longstanding issue about this visuo-motor plasticity is about its specificity to the exposure condition. In contrast to very poor transfer to unexposed effectors classically described in healthy subjects, therapeutic results obtained in neglect patients suggested that PA can generate unexpected "expansion". Prism adaptation affects numerous levels of neglect symptomatology, suggesting that its effects somehow expand to unexposed sensory, motor and cognitive systems. The available body of evidence in support for this expansion raises important questions about the mechanisms involved in producing unexpected cognitive effects following a simple and moderate visuo-motor adaptation. We further develop here the idea that prism adaptation expansion to spatial cognition involves a cerebello-cortical network and review support for this model. Building on the basic, therapeutical and pathophysiological knowledge accumulated over the last 15 years, we also provide guidelines for the optimal use of prism adaptation in the clinic. Although further research and clinical trials are required to precisely define the ideal regime for routine applications, the current state of the art allows us to outline practical recommendations for therapeutical use of prisms.